Integral Airfoil Generation of Multi-rotor Aircraft Based on Optimization of Upper Wing Contour and CFD Simulation - Z. Wang; Y. Zhu; Q. Yuan; W. B. Gu; X. B. Xie (Journal of Applied Fluid Mechanics, 2024)
Regarding the airfoil optimization design of multi-rotor unmanned aerial vehicles, this paper proposes an integral airfoil design method based on upper airfoil contour optimization. Firstly, by designing concave descent input curves with 0-1 distribution, the upper arc of different optimized airfoils is obtained using the Tangent circles method. Secondly, an integral airfoil generation method is developed after establishing the middle arc. As the upper and lower arcs of different shapes are randomly combined, various airfoil profiles are obtained by random assortment. Finally, the effectiveness and accuracy of the designed airfoil are validated through Python programming. The airfoil is generated by the XFOIL program, and the optimal airfoil is output with a lift-to-drag ratio as the target. Meanwhile, an accurate Fluent analysis model is established, and a comparison verification is conducted on the data with the attack angle falling within [-8.02, 12.04] and lift-to-drag ratio falling within [-50, 100]. After Fluent modeling of the designed airfoil, the Euclidean distance between the calculated angle-lift-drag ratio data curve and the data curve tested by the wind tunnel is 0.0331, while the Euclidean distance between the simulated data in the literature and the wind tunnel data is 0.0408. It indicates that our precise model achieves 18.9% higher accuracy than the literature model. Testing and verification results indicate that our designed airfoil based on upper arc optimization and its corresponding airfoil library can meet the design requirements for the aerodynamic performance of airfoils in practical applications. It provides a valuable reference for the development of airfoil design, optimization, and generation methods.